Toward a structome of Acinetobacter baumannii drug targets. (20th January 2020) - Tillery, Logan M.; Barrett, Kayleigh F.; Dranow, David M.; Craig, Justin; Shek, Roger; Chun, Ian; Barrett, Lynn K.; Phan, Isabelle Q.; Subramanian, Sandhya; Abendroth, Jan; Lorimer, Donald D.; Edwards, Thomas E.; et al.
Abstract: Acinetobacter baumannii is well known for causing hospital‐associated infections due in part to its intrinsic antibiotic resistance as well as its ability to remain viable on surfaces and resist cleaning agents. In a previous publication, A. baumannii strain AB5075 was studied by transposon mutagenesis and 438 essential gene candidates for growth on rich‐medium were identified. The Seattle Structural Genomics Center for Infectious Disease entered 342 of these candidate essential genes into our pipeline for structure determination, in which 306 were successfully cloned into expression vectors, 192 were detectably expressed, 165 screened as soluble, 121 were purified, 52 crystalized, 30 provided diffraction data, and 29 structures were deposited in the Protein Data Bank. Here, we report these structures, compare them with human orthologs where applicable, and discuss their potential as drug targets for antibiotic development against A. baumannii .